14-3-3-zeta participates in TLR3-mediated TICAM-1 signal-platform formation. (May 2016) - Funami, Kenji; Matsumoto, Misako; Obuse, Chikashi; Seya, Tsukasa
Highlights: 14-3-3-zeta is a component of TICAM-1 signalosome. TLR3-TICAM-1 pathway is reduced by 14-3-3-zeta knockdown. 14-3-3-zeta participates in TICAM-1 signalosome formation. Abstract: Recognition of pathogen-associated molecular patterns (PAMPs) by pattern-recognition receptors (PRRs) is important in innate immune signaling. Toll-like receptors (TLRs) are well-characterized PRRs and are pivotal in antiviral and antitumor host defense. TIR domain-containing adaptor molecule 1 (TICAM-1, also called TRIF) is an adapter molecule in TLR3- and TLR4-mediated IRF3 activation, late-phase NF-κB activation and MAPK-mediated AP-1 activation. When a TLR3 ligand is added to TLR3-positive cells, TICAM-1 transiently interacts with TLR3 and forms multimers in the cytosol. However, the precise mechanism of TICAM-1 multimer formation remains unknown. In this study, we identified 14-3-3-zeta as a molecule that functions in TLR3-mediated signaling. Knockdown of 14-3-3-zeta reduced production of type I interferon and inflammatory cytokines, nuclear translocation of IRF3 and phosphorylation of IκB via the TLR3-TICAM-1 pathway. Furthermore, TICAM-1 multimerization by ligand stimulation was prohibited by 14-3-3-zeta knockdown. These results suggest that 14-3-3-zeta is involved in the TLR3-TICAM-1 pathway in promoting multimerization of TICAM-1 for the formation of a TICAM-1 signalosome.